Peran Kepemimpinan Transformasional dalam Peningkatan Kinerja Karyawan yang Inovatif - Risma Putri Ashari; Salsabela Bintang Putri M; Mochammad Assyava Aulia F; Nurisa Nurisa; M. Isa Anshori (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Transformational leadership is a key area of focus in leadership studies, aimed at improving innovative employee performance. This leadership style involves inspiring, motivating, and guiding employees towards common goals, resulting in a productive and innovative work environment. Transformational leaders distribute power to subordinates, develop their abilities and self-confidence, and create independent work teams. This research utilizes a qualitative literature review. Literature studies involve searching for and reading existing written sources to obtain a theoretical basis for the problem being researched. The study found that transformational leadership plays an important role in improving employee performance by inspiring, motivating, and guiding them towards common goals. Transformational leadership can increase employee self-confidence, leading to improved performance. It has a more dominant impact on employee performance than communication and work discipline.